Uncorrected myopia significantly increases P100 latency and lowers N75–P100 amplitude in visual evoked potentials (VEP) - Penchha Nembang,; Lokraj Joshi,; Samikshya Bhattarai,; Kshitiz Upadhyay-Dhungel, (Janaki Medical College Journal of Medical Science, 2025)
Background & Objectives: Myopia or short-sightedness is rising globally, particularly among children and young adults with increased screen exposure. Visual evoked potentials (VEPs), measuring latencies and amplitudes, provide an objective assessment of visual pathway. Despite rising prevalence of Myopia, studies investigating its effects on VEPs are very limited in Nepal, adding to the relevance of this study.Materials and Methods: This case-control study enrolled 30 clinically diagnosed myopic individuals (≤ −0.5 D) and 30 age and sex-matched healthy controls with normal vision were recruited following informed written consent. Anthropometric parameters were recorded. Pattern‐reversal VEPs were obtained, with electrodes placed per the 10-20 system of the subjects. Latencies (N75, P100, N145) and amplitudes (N75-P100, P100-N145) were measured. Recordings were done at room temperature (26 ± 2 °C). Data, confirmed to be normally distributed, were analyzed using t-tests in SPSS.Results: Thirty myopic individuals and 30 age-sex matched emmetropic controls were studied. Compared with controls, the myopic group showed significant (p < 0.05) increase in P100 latency (93.5 ± 6.3 Vs 88.7 ± 5.2, p=0.03) and decrease in N75–P100 amplitude (6.5 ± 2.1 Vs 8.2 ± 2.4, p=0.04) in right eye and significant increase in P100 latency (94.2 ± 6.5 Vs 89.4 ± 5.0, p=0.02) and decrease in N75–P100 amplitude (6.3 ± 2.3 Vs 8.0 ± 2.5, p=0.03) in left eye. Trends towards increased N75 and N145 latencies and decreased P100–N145 amplitudes were also observed in the myopic group.Conclusions: Uncorrected myopia significantly delays P100 latency and lowers N75–P100 amplitude in both eyes, with additional trends of delayed N145, N75 latencies and reduced P100–N145 amplitudes, indicating broader impairment of early cortical visual processing.